(1)
since both equations express y in terms of x, equate the right sides
- 2x = - 4x + 10 ( subtract 4x from both sides )
2x = 10 ( divide both sides by 2 )
x = 5
substitute x = 5 into y = - 2x → y = - 10
solution is : (x, y ) → (5, - 10 )
(2)
equate the right sides of both equations
3x = 2x - 7 ( subtract 2x from both sides )
x = - 7
substitute x = - 7 into y = 3x → y = - 21
solution is : (x, y) → (- 7, - 21)
(3)
substitute y = - 8 into the other equation
- 8 = 6x + 22 ( subtract 22 from both sides )
- 30 = 6x ( divide both sides by 6 )
x = - 5
solution is : (x, y ) → (- 5, - 8 )